DIGITAL MARKETING STRATEGY: CASE STUDY AND BEST PRACTICE FOR MSMEs IN RIAU PROVINCE IN THE DIGITAL ERA - Alvionita, Agnes; Rama, Rovanita; Wijayanto, Gatot; Novandalina, Arini; Rivai, Yutiandry (ITB AAS Indonesia Surakarta, 2024)
This research is motivated by the importance of digital marketing strategies in the digital era in increasing product sales to MSMEs in Riau Province. This research aims to explain digital marketing strategies for MSMEs in Riau Province in the digital era. This research uses qualitative methods using Miles and Huberman analysis. This research was conducted on MSMEs in Riau Province where the informants were owners, employees and customers who were determined using purposive sampling. Data collection techniques were carried out using observation, in-depth interviews and documentation. The research was carried out for one month, where the research will be analyzed using the Miles and Huberman method, namely: collecting data, data reduction, data display, and verification. The results of this research explain 1) A case study of digital marketing strategies for MSMEs in Riau Province in the digital era explains that the strategies implemented are marketing via social media, quality content, special promotions on social media, collaboration with local influencers and active customer service, and 2 ) Best practice digital marketing strategies for MSMEs in Riau Province in the digital era include understanding target markets, building online marketing, social media marketing, content marketing, collaboration with local influencers and email marketing.